2010
DOI: 10.3758/mc.38.4.519
|View full text |Cite
|
Sign up to set email alerts
|

Impact of phonology on the generation of handwritten responses: Evidence from picture-word interference tasks

Abstract: The degree to which phonological codes constrain handwriting is at present controversial. Two experiments used a picture-word interference paradigm in which participants wrote down the names of pictures while attempting to ignore visual distractor words presented at various time intervals (SOAs). Distractors could be orthographically and phonologically related, orthographically related only, or unrelated. We found an exclusive effect of phonology at an early SOA, and orthographic priming at a later SOA. In a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
51
0
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 35 publications
6
51
0
3
Order By: Relevance
“…As outlined in the Introduction, this inference broadly agrees with previous studies which also suggested that the exact timing is critical (Qu et al, 2011;Zhang & Damian, 2010;Zhang & Wang, 2015). Qu et al (2014) recently reported EEG evidence suggesting that orthographic and phonological variables in written production have distinct time courses: activation of phonological codes takes place earlier (approximately 100 ms) than access to orthographic codes.…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…As outlined in the Introduction, this inference broadly agrees with previous studies which also suggested that the exact timing is critical (Qu et al, 2011;Zhang & Damian, 2010;Zhang & Wang, 2015). Qu et al (2014) recently reported EEG evidence suggesting that orthographic and phonological variables in written production have distinct time courses: activation of phonological codes takes place earlier (approximately 100 ms) than access to orthographic codes.…”
Section: Discussionsupporting
confidence: 79%
“…They found a similar degree of priming for both conditions at an "early" SOA of 0 ms. At a later SOA (+100 ms), facilitation emerged only for the orthographically and phonologically related condition, but no longer for the phonologically only related condition. As Zhang and Damian (2010) did, Qu et al (2011) concluded that this pattern suggests a role of phonology in written picture naming, and furthermore that phonology might be particularly prominent at early stages of orthographic encoding. The latter (but not the former) part of this suggestion has very recently been called into question by Zhang and Wang (2015) who reported results from picture-word interference experiments, also conducted in Chinese, in which effects of orthographically related, phonologically related, or orthographically and phonologically related distractors were compared.…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…A few studies, however, have found that phonological codes do influence writing (e.g., Bonin et al, 2001b; Zhang and Damian, 2010; Afonso and Álvarez, 2011; Damian et al, 2011; Damian and Qu, 2013; Wang and Zhang, 2015). For example, Zhang and Damian (2010) use a written picture-word interference (PWI) task to examine the role of phonology among English speakers. Distractors were orthographically plus phonologically (OP) related (e.g., picture name: hand ; distractor : sand ), orthographically (O) related (e.g., hand and wand ), or unrelated to picture names.…”
Section: Introductionmentioning
confidence: 99%
“…Here also, the psycholinguistic evidence indicates spoken forms are often active during spelling and may influence spelling performance. For example, studies have found that when individuals are trying to write a word, the simultaneous presentation of a distractor word with a similar/same sound results in faster writing times (relative to an unrelated distractor) than does a distractor with only similar spelling (Zhang & Damian, 2010; Qu et al, 2011). However, as these authors note, the results do not imply that the phonological activation is necessary for accurate single word spelling.…”
mentioning
confidence: 99%